Biofuel Cells: Molecularly Ordered Bioelectrocatalytic Composite Inside a Film of Aligned Carbon Nanotubes (Adv. Energy Mater. 1/2013). Issue 1 (8th January 2013) - Yoshino, Syuhei; Miyake, Takeo; Yamada, Takeo; Hata, Kenji; Nishizawa, Matsuhiko
<x xml:space="preserve">Abstract</x> A molecularly ordered composite film of enzyme, glucose oxidase, and aligned carbon nanotubes shows extremely high activity for oxidation of glucose. This free‐standing, flexible composite film can be wound onto needle devices, to create, for example, an LED‐based "self‐powered sugar indicator", with a blinking interval inversely proportional to the concentration of sugars in fruits. More details can be found in the article by Matsuhiko Nishizawa and co‐workers on page 60. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>